The hydrodynamics of self-rolling locomotion driven by the flexible pectoral fins of 3-D bionic dolphin - Zhihan Li; Dan Xia; Xufeng Zhou; Jiabo Cao; Weishan Chen; Xingsong Wang (Journal of Ocean Engineering and Science, 2022)
The novel autonomous rolling performance is realized by the pair of pectoral fins of a three-dimensional(3-D) bionic dolphin in this paper numerically. 3-D Navier–Stokes equations are employed to simulate the viscous fluid around the bionic dolphin. The effect of self-rolling manoeuvrability is explored using the dynamic mesh technology and user-defined function (UDF). By varying the parameter ratios, the interaction of flexible pectoral fins is divided into two motion modes, amplitude differential and frequency differential mode. As the primary driving source, the differential motion of a pair of pectoral fins can effectively provide the rolling torque, and the trajectory of the entire rolling process is approximately the clockwise spiral. The results demonstrate that the rolling angular velocity and driving torque in the steady state can be improved by increasing parameter ratios, and the rolling efficiency can reach the maximum under the optimal parameter ratio. Meanwhile, different parameter ratios do not affect the rolling radius of the self-rolling dolphin. The evolution process around the pair of pectoral fins is shown by the flow structures in self-rolling swimming, reasonably revealing that self-rolling locomotion is produced by the pressure and wake vortices surrounding the pair of pectoral fins, and the wake structures depend primarily on the variation of parameter ratio. It properly turns out that the application of the pair of pectoral fins can realize the self-rolling performance through parameter differential modes.